Challenges and opportunities of groundwater resources management: Examination of the problematic access to water in Central Valleys of Oaxaca, Mexico - Nava, Luzma Fabiola; Medrano Pérez, Ojilve Ramón (Acta Universitaria, 2019)
Groundwater resources, in addition to being subject to quantitative management mechanisms, are the main source of water supply for certain users. The access, the use and the exploitation of these resources favor the emergence of tensions between governmental and social spheres. The existence of a water withdrawal ban decree and the lack of recognition of the capacity of participation of community actors are factors that potentiate the emergence of conflict. In this sense, organized indigenous leadership favors the formulation of alternative strategies to adapt a long-standing decree. The case of the problematic water access in Central Valleys of Oaxaca teaches us that the great opportunity to adapt groundwater management relies on the community capacities to formulate public policy recommendations aimed at ad hoc water resources management.